2016
DOI: 10.1002/asia.201501253
|View full text |Cite
|
Sign up to set email alerts
|

O6‐Alkylguanine DNA Alkyltransferase Repair Activity Towards Intrastrand Cross‐Linked DNA is Influenced by the Internucleotide Linkage

Abstract: Oligonucleotides containing an alkylene intrastrand cross-link (IaCL) between the O(6) -atoms of two consecutive 2'-deoxyguanosines (dG) were prepared by solid-phase synthesis. UV thermal denaturation studies of duplexes containing butylene and heptylene IaCL revealed a 20 °C reduction in stability compared to the unmodified duplexes. Circular dichroism profiles of these IaCL DNA duplexes exhibited signatures consistent with B-form DNA. Human O(6) -alkylguanine DNA alkyltransferase (hAGT) was capable of repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…Perhaps the 7‐carbon linker may have greater flexibility to adopt a conformation that evades steric clashes in the active site of hAGT. Similar results were found for the repair of intra‐ and interstrand crosslinks, for which the heptamethylene linker was repaired more efficiently than that of the tetramethylene analogue . Crystal structures of hAGT have revealed that its binding channel has a tunnel‐like shape, which allows the entrance and accommodation of larger adducts with the reactive Cys145 located at the end of the tunnel (9 Å deep) .…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Perhaps the 7‐carbon linker may have greater flexibility to adopt a conformation that evades steric clashes in the active site of hAGT. Similar results were found for the repair of intra‐ and interstrand crosslinks, for which the heptamethylene linker was repaired more efficiently than that of the tetramethylene analogue . Crystal structures of hAGT have revealed that its binding channel has a tunnel‐like shape, which allows the entrance and accommodation of larger adducts with the reactive Cys145 located at the end of the tunnel (9 Å deep) .…”
Section: Resultssupporting
confidence: 62%
“…No repair of dFU‐C7OH was observed by Ada‐C (Table ), which may be due to the active site not being capable of accommodating the longer linker. Recently, our group showed moderate repair of an (5′→3′) O 4 ‐T‐heptylene‐ O 6 ‐dG intrastrand crosslink adduct that lacked an intradimer phosphodiester group by Ada‐C . The repair occurred solely at the O 6 position of the dG moiety, and marked one of the first examples in which Ada‐C demonstrated proficiency in the repair of larger alkyl adducts.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group demonstrated that hAGT can repair IaCLs between the O6 positions of neighboring dG residues . IaCL DNA lacking the intradimer phosphodiester group were processed more efficiently by hAGT relative to IaCLs containing the phosphodiester linkage . Moreover, heptylene‐linked IaCLs were more efficiently unhooked/repaired compared to the butylene analogues, following a similar trend observed for the AGT‐mediated repair of ICL DNA.…”
Section: Introductionmentioning
confidence: 58%
“…OGT was capable of repairing larger adducts (4‐hydroxybutylene and 7‐hydroxylheptylene) at the O4 atom of T, whereas hAGT and Ada‐C remained inert towards these substrates. Furthermore, our group demonstrated that the repair reaction of AGT towards adducts at the O6 atom of dG can be harnessed to generate covalently linked site‐specific DNA–protein conjugates with ICL or IaCL DNA . With DNA containing an O 4 ‐T‐heptylene‐ O 6 ‐dG ICL, the O4 atom of a thymidyl residue within the DNA strand can be attached by a heptylene linkage to hAGT .…”
Section: Introductionmentioning
confidence: 99%
“…These studies prompted the investigation of analogous O 6 ‐2′‐deoxyguanosine‐alkylene‐ O 6 ‐2′‐deoxyguanosine IaCL probes (O'Flaherty and Wilds, ). Moreover, modification of the synthetic methodology allowed us to study the effect of absence of the intradimer phosphodiester linkage on repair by AGTs and translesion synthesis using DNA polymerase η (O'Flaherty and Wilds, ; O'Flaherty et al., ; O'Flaherty and Wilds, ).…”
Section: Commentarymentioning
confidence: 99%